PARTISIPASI PETANI PADA PROGRAM KETAHANAN PANGAN DI KABUPATEN KARANGASEM (Studi Kasus Di Subak Sasa, Kelurahan Subagan, Kecamatan Karangasem) - I Gusti Agus Arimbawa; I Ketut Arnawa; Nyoman Yudiarini (AGRIMETA : Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
This research entitled Farmer Participation In Food Security Program In Karangasem Regency, Case Study In Subak Sasa Subagan Village, Karangasem Sub-district. This study aims to determine: (1) farmer participation on food security program; (2) factors related to farmer participation in food security program. This research was conducted in Subak Sasa. Determination of location of research conducted by purposive with base of consideration that Subak Sasa become food security program participant with the most member in Subagan Village. The respondents used census method with 36 respondents. The results showed that: (1) Farmer participation on food security program is in high category; (2) Factors related to farmer participation in food security program are age of farmer, number of family member and land ownership area.